2016
DOI: 10.1016/j.jash.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Gut hormones and gut microbiota: implications for kidney function and hypertension

Abstract: Increased blood pressure (BP) and chronic kidney disease are two leading risk factors for cardiovascular disease. Increased sodium intake is one of the most important risk factors for development of hypertension. Recent data have shown that gut influences kidney function and BP by variety of mechanisms. Various hormones and peptides secreted from gut such as gastrin, glucocorticoids, Glucagon-like peptide-1 impact on kidney function and BP especially influencing sodium absorption from gut. These findings stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 51 publications
0
34
0
1
Order By: Relevance
“…Gut-kidney crosstalk, which is largely affected by the gut microbiota, plays an integral role in the development of CKD with reciprocal interactions [25]. The gut microbiota manipulates the processes leading to CKD through inflammatory [25], endocrine [20], and neurologic pathways [90]; a healthy gut microbiota protects the CKD, whereas gut dysbiosis contributes to the development of CKD [2]. In fact, CKD is associated with alterations in the gut microbiota; species producing uremic toxins, such as Enterobacteriaceae, Clostridiaceae, Pseudomonadaceae, and Bacteroidiaceae, are increased, whereas beneficial species, such as Lactobacillaceae, Bifidobacteriaceae, and Prevotellaceae, are decreased [101][102][103][104].…”
Section: Gut-kidney Crosstalk and Inflammation In The Development Of Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut-kidney crosstalk, which is largely affected by the gut microbiota, plays an integral role in the development of CKD with reciprocal interactions [25]. The gut microbiota manipulates the processes leading to CKD through inflammatory [25], endocrine [20], and neurologic pathways [90]; a healthy gut microbiota protects the CKD, whereas gut dysbiosis contributes to the development of CKD [2]. In fact, CKD is associated with alterations in the gut microbiota; species producing uremic toxins, such as Enterobacteriaceae, Clostridiaceae, Pseudomonadaceae, and Bacteroidiaceae, are increased, whereas beneficial species, such as Lactobacillaceae, Bifidobacteriaceae, and Prevotellaceae, are decreased [101][102][103][104].…”
Section: Gut-kidney Crosstalk and Inflammation In The Development Of Ckdmentioning
confidence: 99%
“…The gut microbiota contributes to the health of the host by protective and trophic functions [6] in addition to aiding host metabolism by synthesizing conjugated linoleic acid [7], amino acids such as lysine [8], vitamin B complex [9], and vitamin K [10] and by facilitating the absorption of complex carbohydrates [11]. Additionally, the gut microbiota communicates with the rest of the body primarily via its interactions with the immune system [12] and its metabolic products, such as uremic toxins [2], oxalate [13], bile acids [14], short-chain fatty acids (SCFAs) [15], nitric oxide (NO) [16], vitamin K [10], vitamin B complex [17], threonine [18], microRNAs (miRNAs) [19], gut hormones [20], neurotransmitters [21], the autonomic nervous system (ANS), and the enteric nervous system (ENS) [22] and through effects on intestinal expression of cannabinoid receptor CB1 [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, Santisteban et al 2 have suggested a more complicated relationship in that they reported that there was a clear shift in the microbiome after the changes in gut permeability developed. Others have reported differences in the microbiome in hypertension 3 so it is clearly not just a matter of allowing access but of also creating a dysbiosis, or an imbalance negatively impacting the beneficial flora of the intestinal tract. How this could occur is not at all clear but, in the current paper, the authors noted that mesenteric blood flow was decreased, a phenomenon that has been long been associated with increased intestinal permeability.…”
mentioning
confidence: 99%
“…Gut microbial metabolites, such as short‐chain fatty acids (SCFAs), were found to influence host physiological functions including blood pressure . SCFAs influence blood pressure via activating sensory receptors such as olfactory receptor 78 (Olfr78), GPR41, and GPR43 . Olfr78 is expressed well in the renal juxtaglomerular apparatus, where activation of Olfr78 induces renin secretion.…”
Section: The Role Of Gut Microbiota In the Regulation Of Gastro‐renalmentioning
confidence: 99%